(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Sondak CFA, Kaligis EY. 2022. Assessing the seagrasses meadows status and condition: A case study of Wori Seagrass Meadows, North Sulawesi, Indonesia. Biodiversitas 23: 2156-2166. Seagrass meadows play an important role in the coastal ecosystem through the services they provide, however, they are one of the most threatened ecosystems in the coastal environment due to anthropogenic influences and rapid environmental changes. Seagrass meadows extent is not validated and the health condition is left unmonitored and unreported. In Indonesia, the information about the current status of seagrass meadows’ extent and health conditions is limited. We assess the seagrass meadow abundance, status, and health condition. We provide information about species abundance, density threats, and the health status of seagrass meadows in North Sulawesi, Indonesia, particularly in Wori District. This district has a vast extent of seagrass meadows but has been affected by the expansion of the industrial/tourism area within the region. This study found that seagrass meadows’ coverages were moderate, but their health status was unhealthy. Six seagrass species are found in this area, including Enhalus acoroides (L.f.) Royle, Thalassia hemprichii (Ehrenb.) Aschers, Cymodocea rotundata (Asch. & Schweinf.), Halodule pinifolia (Miki) Hartog, Halophila ovalis (R.Br.) Hook. F., and Syringodium isoetifolium (Asch.) Dandy. Our results highlight the communities’ activities, including gleaning, boat propeller, anchoring, mooring, sedimentation, and the effects of climate change on the environment as factors that could affect seagrass meadows’ extent and health condition in the study sites.